2020
DOI: 10.1002/app.49138
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐modified CNFs, GPs, and their mixtures for enhanced polypropylene thermal conductivity

Abstract: Low thermal conductivity of polypropylene (PP) is a key factor in limiting its use for the manufacture of solar heaters. To overcome this problem, in the present work, two different methods were tested to increase the thermal conductivity of a PP matrix by increasing the dispersion and compatibility between PP and carbon nanoparticles (CNPs). In the first method, CNPs modified superficially by plasma of propylene were used, and in the second, mixtures of CNPs (carbon nanofibers and graphene platelets in 9:1, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] Fundamentally, these micro/nanofillers could enhance the polymer's TC via forming continuous thermal conductive pathways in composites. 21,22 Some studies reported that the filler's size and content significantly influenced the formation of thermal conductive networks. 23,24 On the one hand, the fillers with larger sizes benefited for lower thermal interfacial resistances and higher TCs, due to their fewer contact interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20] Fundamentally, these micro/nanofillers could enhance the polymer's TC via forming continuous thermal conductive pathways in composites. 21,22 Some studies reported that the filler's size and content significantly influenced the formation of thermal conductive networks. 23,24 On the one hand, the fillers with larger sizes benefited for lower thermal interfacial resistances and higher TCs, due to their fewer contact interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, many researchers have fabricated polymer composites by incorporating micro/nanofillers with high TCs into the polymer matrix, such as metal particles, 7,8 graphene nanosheets, 9,10 carbon nanotubes, 11 and boron nitride nanosheets (BNNs) 12–20 . Fundamentally, these micro/nanofillers could enhance the polymer's TC via forming continuous thermal conductive pathways in composites 21,22 . Some studies reported that the filler's size and content significantly influenced the formation of thermal conductive networks 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, CNPs [P], load transfer with the polymer occurs through van der Waals or π-interactions, weaker than the hydrogen and covalent bonding presented by CNPs [M]. 53,54 The differences mentioned above in compatibility were also studied by Raman analysis in a previous study (Covarrubias et al 15 ); the compatibility was related to the intensity of the 2D band associated with tangential vibrations (carbons with sp 2 hybridization). The signal of the tangential vibrations related to carbon atoms with sp 2 hybridization dissipated when the surface of the CNPs interacted with the PP matrix.…”
Section: Compatibility Of Cnps With Pp Matrixmentioning
confidence: 99%
“…4,14 It is well known that surface treatments of the CNPs can increase compatibility. [15][16][17][18][19] However, the most modification methods require long periods of exposure of the CNPs to chemical substances that are aggressive with the surface and have solventassociated problems, such as environmental problems and solvent disposal costs. From an industrial point of view, where mass production is a priority, these approaches lead to substantial economic and environmental issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation